OCD-graphene: a 2D carbon allotrope with high theoretical capacity for sodium-ion batteries - Martins, Nicolas F. [UNESP]; Laranjeira, José A. [UNESP]; Sambrano, Julio R. [UNESP] (Elsevier, 2025)
The performance of the newly designed octagonal-distorted two-dimensional (2D) material, named OCD-graphene, as an anode for sodium-ion batteries (SIBs) is systematically studied using density functional theory (DFT) simulations. The OCD-graphene monolayer exhibits robust dynamic and thermal stability, confirmed by phonon dispersion and ab initio molecular dynamics (AIMD) calculations. This structure shows a significant mechanical response, following the Born-Huang stability criteria. The single Na atom preferentially binds to the octagonal-distorted ring of OCD-graphene with an adsorption energy ( E ads ) of −1.64 eV. Full sodiation results (24 Na atoms) yielding a remarkable capacity of 1339 mAh/g, superior to many traditional anode materials. The E ads ranges from −1.49 eV to −0.58 eV, indicating favorable Na interaction with the sheet and suitable charge transfer. AIMD simulations confirm the stability of the system at 300 K. Additionally, Na mobility across OCD-graphene is facilitated by a low migration barrier of 0.12 eV and a high diffusion rate (D ≈ 9.72 × 10−3). The electrochemical stability of the Na electrode is verified within a suitable open circuit voltage range (1.49–0.40 V). These findings highlight the potential of OCD-graphene as a high-performance anode material for SIBs, paving the way for further research.